Implementação de malha de controle de Força-G acoplada à malha de controle de umidade em peneira vibratória - Pereira Junior, Wagner Vicente (2021)
The drilling process of an oil well is composed of several sub-processes, including solids control, in which the gravel coming from the well is separated from the drilling fluid that was injected mainly to lubricate and cool the drill during drilling. This fluid must be reconditioned to be reused, going through several separation steps, the first of which is the vibrating sieving step, which can be considered the most important, since other solids separation equipment can operate efficiently only if this step is working properly. The objective of this work was to evaluate the vibratory sieving process and verify how the moisture content behaves against the effect of independent variables in stationary conditions and also to evaluate the effect of g-force in transient regimes. Using a slurry formed by a suspension of sand, water and xanthan gum (with density and rheology similar to the real fluid), a central composite plan was made with two replicas at the central point, totaling 16 experiments. Thus, a model was identified that represents the behavior of the moisture content at steady state against the independent variables: g-force, screen inclination and feed flow. The moisture content was directly proportional to the g-force and feed flow variables, and inversely proportional to the slope variable. The operating point of the sieve that provided less moist solids was g-force (1.3), inclination (2.5º) and mud flow (55.9 kg/min). The sieve operating point that provided the wetter solids was g-force (2.3), slope (2.0º) and mud flow (300.0 kg/min). The static model identified together with a dynamic g-force model obtained experimentally were used to simulate the effect of the steady-state g-force variable in the Simulink™ environment of the Matlab™ application, adopting a slope of 2° and a flow rate of 76.5 kg/h. Thus, it was possible to define a g-force control strategy based on a humidity set point and adjust the parameters for possible disturbances imposed on the system.